MORPHOLOGICAL AND BIOCHEMICAL CHANGES IN THE PROCESS OF HEALING OF BURN WOUNDS WITH OINTMENTS BASED ON CARBOXYMETHYL CHITOSAN APIS MELLIFERA - Kurbonova , F.N.; Samandarova М.О. (Educational Research in Universal Sciences, 2023)
This article presents the results of obtaining biopolymers of carboxymethyl esters of chitosan from a new promising source - dry dead bees. Dried and crushed deadwood, collected during the spring renewal of the bee colony, was used. The process was carried out under general conditions according to the general method of alkylation. Provides information about thermal skin burns and emerging pathophysiological changes in integumentary tissues. The aim of studying and treat these severe processes, burn the skin of animals. A new model of thermal skin injury in rats has been created. For the occurrence of a skin burn, a soldering gun with a flat rod PP REXANT ZD-715 12-0188 with a tip heating temperature of up to 400 0C was used. The degree of the burn was determined by histological examination of skin tissues under a microscope, which was grade IIIA and IIIB. Positive results of using an ointment based on carboxymethylchitosan (CMXZ) have been recorded.